Using solar photovoltaic energy in urban water supply systems: a case study in Kayseri, Turkey. Issue 5 (9th April 2022) - Sekmen, Ufuk; Yildiz, Omer Faruk; Yilmaz, Mehmet; Ozdemir, Ozgur
Abstract: Submersible pumps, widely used in deep wells drilled to meet the water needs of users in urban areas, add an additional load to the conventional electricity grid infrastructure and are responsible for increasing the concentration of greenhouse gas emissions in the atmosphere. The main objective of this study is to investigate the technical and economic feasibility of using solar photovoltaic (PV) energy to reduce the net power drawn from the grid by submersible pumps in urban water supply systems. The Germiraltı catchment area (Kayseri, Turkey), which provides all of its energy needs from the city electricity grid, was chosen as the research area. Two different scenarios, 'hybrid-powered water pumping system' and 'grid-connected PV system', were analyzed and evaluated. A 1, 620 kWp grid-connected PV system can inject 2, 787.8 MWh/year of energy into the grid, which is more than the total annual energy need of the submersible pumps. The system operates with 85.7% performance ratio (PR), 19.6% capacity factor (CF) and 4.71 (h/d) final yield. The payback period of the system is calculated as 4.1 years. The results show that it is economically competitive to meet the energy needs of submersible pumps in urban water supply systems with solar PV energy. HIGHLIGHTS: Submersible pumps, which have been widely used in urban water supply systems, consume a considerable amount of energy. Feasibility of using solar PV energy in urban water supply systems is investigated. Two scenarios, 'hybrid-powered water pumping system' and 'grid-connected PV system', are analyzed and evaluated. The grid-connected PV system is found to be a more feasible and viable alternative for Germiraltı catchment area.